2005
DOI: 10.2337/diabetes.54.7.1926
|View full text |Cite
|
Sign up to set email alerts
|

A High-Fat Diet Coordinately Downregulates Genes Required for Mitochondrial Oxidative Phosphorylation in Skeletal Muscle

Abstract: Obesity and type 2 diabetes have been associated with a high-fat diet (HFD) and reduced mitochondrial mass and function. We hypothesized a HFD may affect expression of genes involved in mitochondrial function and biogenesis. To test this hypothesis, we fed 10 insulinsensitive males an isoenergetic HFD for 3 days with muscle biopsies before and after intervention. Oligonucleotide microarray analysis revealed 297 genes were differentially regulated by the HFD (Bonferonni adjusted P < 0.001). Six genes involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
454
8
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 541 publications
(496 citation statements)
references
References 37 publications
32
454
8
2
Order By: Relevance
“…Maternal LP diet induced up to threefold changes in the relative expression level of several genes, a finding which was also observed in other gene expression analyses of diet manipulation [29]. These changes are smaller than those observed in islets exposed to acute stress, e.g.…”
Section: Discussionsupporting
confidence: 77%
“…Maternal LP diet induced up to threefold changes in the relative expression level of several genes, a finding which was also observed in other gene expression analyses of diet manipulation [29]. These changes are smaller than those observed in islets exposed to acute stress, e.g.…”
Section: Discussionsupporting
confidence: 77%
“…In this context, we and others have shown that an acute elevation of circulating plasma NEFA levels in humans reduces the gene expression of PPARGC1A [20,21]. In a more chronic approach, Sparks et al [22] revealed that a 3-day high-fat diet decreased the expression of oxidative genes, as well as PPARGC1, in healthy human individuals. A separate experiment in mice showed similar results at the protein level after a 3-week high-fat dietary intervention [22].…”
Section: Introductionmentioning
confidence: 75%
“…Earlier findings in this context have rendered controversial results. Thus, Sparks et al [22] showed a decrease in PPARGC1A mRNA and protein levels after high-fat feeding, both in humans and mice. In addition, we and others previously reported that the infusion of a lipid emulsion in humans leads to a decrease in PPARGC1 gene expression [20,21], while suppression of plasma free fatty acids during exercise by a pharmacological agent increases the expression of PPARGC1A in skeletal muscle [39].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that high-fat diets down-regulate PPARGC1A as well as genes coding for proteins of the electron transport chain in human skeletal muscle, but these observations were never linked to an epigenetic mechanism. 25 Interestingly, PPARGC1A is a coactivator wherein biological and physiological functions are particularly centered on striated muscle, liver, and heart, a triad of organs particularly relevant to the pathophysiology of IR and its cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%